Gut Microbiota (IntechOpen, 2026)
This book on human gut microbiota presents original ideas and the results of new research conducted in experimental and clinical scientific laboratories worldwide. The research results obtained convincingly demonstrate the great importance of the problem under study, not only in terms of new data on the fundamental mechanisms of the human body's interaction with the microcosm inhabiting it, but more importantly, in terms of identifying genuine opportunities to manage these mechanisms and subsequently implement them in clinical practice, which will contribute to improving the survival rates of patients with various diseases and pathological conditions, including critically ill patients at the highest risk.